Association of Different Body Mass Index with Vitamin D Receptor Gene in Females with Deficiency of Vitamin D - Maha F. Smaism (Journal of Global Pharma Technology, 2017)
Background: Obesity is one of the well spread chronic condition that is affecting health and it is connected to many fatal chronic diseases like cardiovascular disease, diabetes mellitus and cancers. Vitamin D is shown to has a role in the pathogen city of obesity, and the Vitamin D receptor (VDR) gene polymorphism is shown to affect the obesity phenotypes like body mass index (BMI).Objective: is to assess the association between different variants of vitamin D receptor gene and the BMI in females with deficiency of vitamin D. Methods and Materials: The study was conducted with the participation of 170 females who are having low vitamin D levels. The single nucleotide polymorphism Taq in the vitamin D receptor gene was detected by PCR-RFLP. Vitamin D level in the serum was measured by ELISA technique. Result: This study is resulted in that there is a positive correlation between the BMI and different biochemical measurements like the level of vitamin D(p < 0.001), calcium level [ both free Ca(p=0.01) and total Ca(p= 0.002)], urea level (p < 0.001), and bilirubin level (p < 0.001). It is also resulted in finding a positive correlation between the BMI and the genotype of the vitamin D receptor, as it is noticed that 44.7% of the patients who are carrying the TT genotype, while only 40.0% of the patients who are carrying the CC genotype. Conclusion From the result the study show significantly negative correlation between Vitamin D and BMI that means the vitamin D deficiency could relate with increase BMI ,Also there is significantly negative correlation between vitamin D and cholesterol ,as well as this study indicate that significantly decrease of total bilirubin with increasing BMI increased. From the results of genetic study for vitamin D receptor gene study, can conclude that the T allele is positively correlated to the obesity represented by the BMI, and that could lead to the conclusion that females who are having the TT genotype are of higher probability to get high BMI and obesity.